INTRODUCTIONS TO SCIENCE RESEARCH PAPERS: BASIC PRINCIPLES, STRUCTURE AND COMPOSITION - Natalia G. Popova (Высшее образование в России)
This paper addresses issues involved in creating the introduction section of IMRAD science research papers in the English language. The introduction is considered as an independent text, which contains comprehensive information about the entire research. The basic principles of the structure and composition of the introduction are described in terms of the requirements imposed by modern peer!reviewed scientific journals. The suggested approach can also be useful when writing an introduction in other languages.Keywords: science research paper introduction, academic text, writing academic